2021
DOI: 10.7759/cureus.15681
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based, Cross-Sectional Study Assessing the Level of Awareness and Insight Related to Cardiovascular Diseases

Abstract: The disease outcome had been shown to improve with improving patient knowledge. The study had two objectives, firstly to assess the level of knowledge about cardiovascular diseases (CVDs) in the general population, and secondly, to provide written educational material regarding the risk factors, major symptoms, and the prevention of CVDs. MethodThe target population was the residents living in the Western region of Saudi Arabia, aged 18 years and above. All were invited to participate voluntarily. A pre-struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 17 publications
2
12
1
Order By: Relevance
“…The current study revealed that CVDs risk factors are common among study participants. These results are supported by other studies in Saudi Arabia (Alghamdi et al, 2021) and Lebanon (Fahs et al, 2017). The main finding of this study is that the majority of study participants were eating an unhealthy diet, being overweight or obese with a BMI of 25 Kg/m 2 and more, and physically inactive.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current study revealed that CVDs risk factors are common among study participants. These results are supported by other studies in Saudi Arabia (Alghamdi et al, 2021) and Lebanon (Fahs et al, 2017). The main finding of this study is that the majority of study participants were eating an unhealthy diet, being overweight or obese with a BMI of 25 Kg/m 2 and more, and physically inactive.…”
Section: Discussionsupporting
confidence: 91%
“…Family history of CVD, dyslipidemia, hypertension, and diabetes was less frequently identified by participants as risk factors for developing CVDs. These results are congruent with those of studies conducted in Saudi Arabia (Alghamdi et al, 2021; Mujamammi et al, 2020), Kuwait (Awad & Al-Nafisi, 2014), and Jordan (Mukattash et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Compared with a community based cross sectional study in the Western region of Saudi Arabia, the majority (80%) indicated lack of exercise, stress, and obesity as the most important risk factors. 77% of participants reported hypertension as a risk factor of CAD, 75.2% for smoking, 73.7% for family history of cardiovascular diseases, 72% Unhealthy diet, 70.4% Previous heart attack and 79.3% know that high level of LDL Cholesterol as a risk factor of CAD (Alghamdi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%